Green Cosmetics : Sejauh Mana Tren Sustainable Beauty Mempengaruhi Niat Pembelian Generasi Muda? - Novita, Novita; Kamul, Imori (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study was conducted to determine the effect of environmental concern, attitude towards green products, and willingness to pay from users of beauty products from the younger generation in Indonesia on the intention to buy environmentally friendly beauty products. Approach: This research uses a quantitative approach. Data collection was carried out using an online questionnaire on users of beauty products through the beauty community on social media. The research data was analyzed using SEM-PLS using the Warp PLS 7.0 application. Research Finding: The results showed a significant positive effect between environmental concern and attitude towards green products. However, the results are not significant in the influence of environmental concern and green purchase intention. This study also found a significant positive effect between attitude towards green product and willingness to pay, the relationship between attitude towards green product and green purchase intention, and the relationship between willingness to pay and green purchase intention. Theoretical contribution/Originality: This research provides a theoretical contribution through the utilization of sustainable beauty trends in the younger generation who are starting to show increased environmental awareness. Practitioner/Policy implication: This research contributes to the beauty industry to focus on creating products that have minimal environmental impact, especially for the younger generation target market. Research limitation: This research is limited to young generation consumers (millennials and generation Z) and the research only focuses on beauty products.